MULTIVARIATE LOGISTIC MODEL OF HOSPITAL LENGTH OF STAY CLINICAL PREDICTORS AFTER APPENDECTOMY: Multivariate Logistic Model Of Length Of Stay After Appendectomy - Doklestić, Krstina S; Lončar, Zlatibor; Bukumirić, Zoran (Medical Research, 2022)
Background  Appendectomies are interesting because they are the most common emergency abdominal operations, they are considered a simple procedure, and imperative is a quick recovery measured by hospital length of stay (LOS). But this is not always the case in clinical practice, hospitalization can be prolonged, and the question is which factors affect it.MethodsA multivariant logistic model of LOS predictors analyzed from clinical data of 446 patients who underwent appendectomy at the Clinic for Emergency Surgery, Belgrade. Patients were divided into Short LOS group (SLOS hospital stay ≤3 days, 157 patients) and in Long LOS group (LLOS hospital stay >3 days, 289 patients).ResultsSignificant differences were detected between group SLOS and LLOS in age (p
Keywords: Hospital Length of Stay (LOS), Laparoscopic Appendectomy (LAP) Mini-Incision Open appendectomy (MIOA)